Performance of Sida hermaphrodita and silphium perfoliatum in Europe: Preliminary results - Facciotto, Gianni; Bury, Marek; Chiocchini, Francesca; Cumplido-Marin, Laura; Czyż, Henryk; Graves, Anil; Kitczak, Teodor; Martens, Reent; Morhart, Christopher; Paris, Pierluigi; Nahm, Michael (Cranfield University, 2018)
This paper reports preliminary results on growth and biomass production of two perennial herbs, Sida hermaphrodita (Virginia Mallow) and Silphium perfoliatum (Cup Plant), tested in the frame of SidaTim project (FACCE-SURPLUS) in German, Italy, Poland and UK. Sida can be used for energy or as a basic compound for various material products, such as fibre products or particle board. Silphium can be alternative to maize for biogas production.